What is the impact of short- and long-term supplementation of either cabergoline or clarithromycin on resolving rat ovarian hyperstimulation syndrome (OHSS) model? - Atilgan, Remzi; Pala, Sehmus; Yavuzkir, Seyda; Baspinar, Melike; Yilmaz, Mustafa; Ilhan, Nevin (Taylor & Francis Inc, 2019)
This study aimed to evaluate the effects of coasting, cabergoline and clarithromycin in a rat ovarian hyperstimulation syndrome (OHSS) model. The 42 female Wistar rats were divided into seven groups: control, OHSS (was given 10 IU of pregnant mare serum gonadotropin for 4 consecutive days from day 22 and 30 IU hCG on the fifth day to induce OHSS ), coasting (hCG was applied on the 27th day after gonadotropin injections and the rats were decapitated on the 28th day), Cabergoline (100 mg/kg/d) and clarithromycin (100 mg/kg/d) were given (on the 26th day) with a short-term supplementation (on the 26th day) and long-term supplementation (from the 22nd to the 26th day) groups. The rats were decapitated on the 27th day. Cabergoline and clarithromycin significantly lowered VEGF-2 levels. Clarithromycin significantly reduced IL-1b and TNF-a and significantly increased IL-10 levels. Clarithromycin may be an effective drug for the treatment of OHSS.
Keywords: Ovarian hyperstimulation syndrome; cabergoline; clarithromycin; coasting